“When you know your name, you should hang on to it”: The Power of Names in Toni Morrison’s Song of Solomon - Dias, Ana Teresa (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
Names and the act of naming are an important part of Toni Morrison’s Song of Solomon. Characters’ names are filled with meaning and are a crucial part of the characters’ personal and collective identity. The plot of the novel, spanning several decades, is largely told through flashbacks thus providing the story of many generations of the Dead family. This allows for the understanding of how names influence several generations of the same family as they can be representative of tradition and heritage but also trauma. This paper is divided in two parts: first, the origin of some names will be detailed with an explanation of its symbolism; then I will delve into the power that each name has within the plot and the narrative of the novel.